The Shape of the Heliosphere Derived from the IBEX Ribbon - Shuai Zhang; Kaijun Liu; Quanqi Shi; Anmin Tian; Fei Yao (The Astrophysical Journal Letters)
The shape of the heliosphere remains largely uncertain due to the lack of in situ measurements. However, the energetic neutral atom (ENA) ribbon structure discovered by the Interstellar Boundary EXplorer (IBEX) satellite provides a new perspective. The present study reveals that the IBEX ribbon ENA flux, observed over a full solar cycle, correlates well with the solar wind ion flux measured at 1 au after a time delay of a few years. The time lag between the two can be used to estimate the heliopause distance and the heliosphere shape. The results show that the heliopause distance is shortest slightly south of the nose direction (∼100 au) and remains almost constant with the ecliptic longitude. However, the distance extends to ∼800 au toward the polar region, and it seems that there is no broadly symmetrical and elongated single heliospheric tail. While these features are consistent with the “croissant-like” model (no tail, but with two jet-like tail lobes) of the heliosphere, they cannot fully exclude the traditional “comet-like” model with a strong local interstellar medium magnetic field. Additional data and modeling are needed to ascertain the precise shape of the heliosphere.